The use of art therapy interventions in schools to support schoolchildren in their health and well-being - B. Faltová; A. Mojžíšová (Medičnì Perspektivi, 2023)
The paper explains the importance of art therapy interventions implemented in the school settings to support schoolchildren’s health and well-being. The aim is a literature review as part of a dissertation at the University of South Bohemia in České Budějovice, Czech Republic, which deals with the possibilities for promoting well-being in schoolchildren, meeting their health and psychosocial needs in the context of their school and family environment. The Czech Republic lacks research on the direct implementation of art therapy interventions into the school environment, and the use of art therapy approaches within the Czech school context is unclear. Data for the literature search were obtained from recent Czech and international publications. We used the EDS multi-finder to search for literature sources. The document search was completed for the 2011–2023 period in Czech and English language. Search terms included School based art therapy, art therapy intervention, art therapy and schoolchildren’s mental health, and schoolchildren’s well-being. According to the results of the analysed literature, it is possible to conclude the benefits of art therapy interventions in schools as part of a holistic supportive approach of schools to their pupils and the environment in which they live. Art therapy, as a non-pharmacological medical complementary and alternative therapy, is considered as both prevention and an opportunity to address the acute need to support schoolchildren in their health and well-being. Art therapy interventions in the school setting can offer help in addressing a wide range of problems of schoolchildren, such as mental health issues, uncertainty in forming a child’s identity, overcoming communication difficulties, addictive behaviours, anxiety, depressive moods associated with acute trauma, family conflicts, truancy and school failure. Art therapy interventions in the school setting can boost feelings of safety in the school environment along with comprehensive psychological, educational, and social interventions synthesizing the needs of the child, teacher, parents and other professionals working together to support the health and well-being of schoolchildren.